Analysis of the Situation on Anthrax in the World in 2022, the Forecast for the Russian Federation for 2023 - A. G. Ryazanova; O. N. Skudareva; D. K. Gerasimenko; F. V. Logvin; L. Yu. Aksenova; O. V. Semenova; E. I. Eremenko; T. M. Golovinskaya; G. A. Pechkovsky; A. N. Kulichenko (Проблемы особо опасных инфекций, 2023)
The paper provides the results of analysis of the epizootiological and epidemiological situation on anthrax in the world in 2022, also, the forecast of incidence rates for the Russian Federation in 2023 is presented. In 2022, two cases of anthrax in farm animals and two cases of cutaneous form of infection in humans were registered in Russia, in the constituent entities of the North Caucasian Federal District: the Republic of Dagestan and the Stavropol Territory. The tense situation on anthrax was reported in the neighboring countries: Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan, and Ukraine. Epizootics of infection with the highest number of affected farm and wild animals were recorded in the countries of Africa, Asia, North America and Europe. The incidence of anthrax among people in the far abroad (mainly in Africa and Asia) was mostly associated with consuming the meat of sick and fallen farm animals, contact with infected animals, animal products. The incidence of anthrax in animals and humans in the Russian Federation in 2023 will largely depend on the scale of coverage with specific immunization of susceptible animals and persons at risk of infection and, given the strict implementation of comprehensive surveillance measures, will be limited to the registration of potentially possible single cases of infection.